2017
DOI: 10.1371/journal.pone.0178404
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of high-mobility group box 1 and soluble receptor for advanced glycation end products in primary antiphospholipid antibody syndrome patients

Abstract: IntroductionMany studies have demonstrated elevated circulating levels of high-mobility group box 1 (HMGB1) and decreased circulating levels of soluble receptor for advanced glycation end products (sRAGE) in patients with autoimmune diseases. In the present study, we investigated plasma levels of both HMGB1 and sRAGE in primary antiphospholipid syndrome (pAPS) patients.MethodsWe prospectively recruited 11 pAPS patients, 17 antiphospholipid antibody (APA)-positive SLE patients without APS manifestations (APA+SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…On the other hand, a previous study demonstrated no significant difference in plasma levels of HMGB1 between adult SLE patients with antiphospholipid antibodies and those with antiphospholipid antibody syndrome (APS) and healthy controls. The authors explained this by interference of anti‐HMGB1 antibodies during ELISA measurement and that anti‐HMGB1 is associated with low serum HMGB1 . However, the present study and several others used the ELISA technique for HMGB1 measurement and did not demonstrate that finding.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, a previous study demonstrated no significant difference in plasma levels of HMGB1 between adult SLE patients with antiphospholipid antibodies and those with antiphospholipid antibody syndrome (APS) and healthy controls. The authors explained this by interference of anti‐HMGB1 antibodies during ELISA measurement and that anti‐HMGB1 is associated with low serum HMGB1 . However, the present study and several others used the ELISA technique for HMGB1 measurement and did not demonstrate that finding.…”
Section: Discussioncontrasting
confidence: 80%
“…On the other hand, a group of investigators reported that serum HMGB1 was not correlated with markers of SLE flare in their pediatric SLE series . One study even reported lower plasma levels of HMGB1 in adult SLE patients during disease flares with inverse correlation between plasma levels of HMGB1 and serum anti‐dsDNA titers …”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the receptor has a different role in the initial and progressive stage of the disease [ 47 , 48 ]. In addition, patients with SLE who have antiphospholipid antibodies (APA) or antiphospholipid syndrome (APS) have shown a decrease in sRAGE plasma levels compared to control [ 53 ]. sRAGE level is associated with leukocytes lymphocytes, neutrophils and monocytes number and with C4 levels, but it does not correlate with the presence of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…We prospectively enrolled 42 patients that included 12 pAPS patients, 17 APA + SLE patients and 13 APS + SLE patients. Most of them had also participated in our previous study on APS patients regarding plasma levels of high‐mobility group box 1 (HMGB1) and soluble receptor for advanced glycation end products (sRAGE) in APS patients . APS was diagnosed based on the revised Sapporo classification criteria .…”
Section: Methodsmentioning
confidence: 99%
“…As described in our previous study, serum anticardiolipin antibodies (ACA) and anti‐β2‐glycoprotein I antibodies were measured by the enzyme‐linked immunosorbent assay (ELISA) kits (INOVA Diagnostics, Inc, San Diego, CA). Lupus anticoagulant was determined by the clot detection method (Beckman Coulter, Inc, Brea, CA).…”
Section: Methodsmentioning
confidence: 99%